Analisis Sentimen Masyarakat Terhadap Permasalahan Keracunan Program Makan Bergizi Gratis (MBG) pada Sosial Media ‘X’ - Anggraeni, Meita Dwi; Yudiananta, Alfian Chandra; Arifin, Azizah Hasna; Arifin, Wafi (STMIK BINA PATRIA, 2025)
The Free Nutritious Meal Program introduced by President-elect Prabowo Subianto has garnered public attention and sparked a variety of responses, both positive and negative. The Free Nutritious Meal Program (MBG) is part of the Indonesian government's policy aimed at improving public nutrition, the welfare of school-going children, and the quality of human resources from an early age. However, during its implementation, several problems have emerged, including cases of food poisoning in several areas. Understanding public perception of these problems is important in order to evaluate the program's success. This study aims to analyze public sentiment towards the MBG program on social media